Pengaruh Tegangan Listrik Dan Konsentrasi Larutan Elektrolit Pada Proses Pemurnian Timah (Sn) Berdasarkan Metoda Electrolytic Refining di Unit Metalurgi PT. Timah Tbk, Mentok, Bangka Barat, Bangka Belitung. - Bayu Muhammad Ilham; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Timah Tbk (TINS) is the largest tin producer in the World. One of the products produced by TINS is tin with 99.99% Sn content, it is the result of the electrolytic refining process with electrolysis method. Electrolysis is influenced by several factors such as electric current and voltage, electrode dimensions, pH and the concentration of the electrolyte solution used. This research has aim to determine the appropriate values of voltage and electrolyte concentration values to optimize the tin (Sn) electrolysis process. The research was carried out in two stages experiment using electrolyte Stannous Chloride (SnCl2) dissolved with Hydrochloric Acid (HCl) and Aquadest. The first with the voltage values of 6, 9, and 12 volts at the electrolyte solution concentration of 0.001 M, the reduced Sn mass was 0.04257, 0.0885, and 0.1182 grams. The next with the electrolyte solution concentration of 0,002, 0,003, 0,004 and 0,005 M at the voltage 12 Volts, the reduced Sn mass was 0,1620, 0,2005, 0,3318 and 0,4158 grams. It is known that the optimal electrolysis process is with a voltage of 12 Volts and a electrolyte solution concentration of 0.005 M. This shows the effect of increasing voltage and electrolyte solution concentration values, will optimize electrolysis process.Keywords: Electrolysis, Electrolyte Solution Concentration, Electrolytic Refining, Tin, Voltage.